OsAPX1 Positively Contributes to Rice Blast Resistance - Sheng, Cong; Yu, Dongli; Li, Xuan; Yu, Hanxi; Zhang, Yimai; Saqib Bilal, Muhammad; Ma, Hongyu; Zhang, Xin; Baig, Ayesha; Nie, Pingping; Zhao, Hongwei (Frontiers in Plant Science, 2022)
Ascorbate peroxidases (APXs) maintain cellular reactive oxygen species (ROS) homeostasis through their peroxidase activity. However, here we report that OsAPX1 also promotes ROS production such that a delicate cellular ROS homeostasis is achieved both spatially and temporally after M. oryzae infection. In brief, OsAPX1 specifically induces apoplastic ROS production through increase respiratory burst oxidase homologs (OsRBOHs) expression and can be inhibited by DPI, an apoplastic ROS inhibitor. The time-course experiment data show that the simultaneous induction of OsAPX1 and OsRBOHs leads to apoplastic ROS accumulation at an early stage; while a more durable expression of OsAPX1 leads to ROS scavenging at a later stage. By the temporal switching between ROS inducer and eliminator, OsAPX1 triggers an instant ROS burst upon M. oryzae infection and then a timely elimination of ROS toxicity. We find that OsAPX1 is under the control of the miR172a-OsIDS1 regulatory module. OsAPX1 also affects salicylic acid (SA) synthesis and signaling, which contribute to blast resistance. In conclusion, we show that OsAPX1 is a key factor that connects the upstream gene silencing and transcription regulatory routes with the downstream phytohormone and redox pathway, which provides an insight into the sophisticated regulatory network of rice innate immunity.